Oxcarbazepine-induced Stevens Johnson syndrome: A rare case report - S R Sharma; Nalini Sharma; M E Yeolekar (Wolters Kluwer Medknow Publications, 2011)
Although carbamazepine is the most common cause of Stevens Johnson syndrome (SJS) a new antiepileptic drug, oxcarbazepine which is structurally related to carbamazepine, has also been rarely shown to induce SJS. Here we report a case with SJS, which was induced by oxcarbazepine.